PENGARUH DEBT TO EQUITY RATIO (DER), NET PROFIT MARGIN (NPM), DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2016 - Redka Rezki Anggraeni (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to analyze the influence of Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Earning Per Share (EPS) simultaneously or partially to the stock price of chemical manufacturing companies listed in Indonesia Stock Exchange 2010- 2016. The nature of this study is correlational research. The population is a subsector of chemical companies listed on the stock exchange indonesia 2010-2016. Samples of research as many as 5 companies of chemical subsector obtained by sampling technique that is purposive sampling. Data collecting technique using documentation method, while data analysis technique using multiple linear regression analysis supported by classical assumption test that is normality test, multicolinearity test, heteroscedasticity test, and autocorrelation test. The results showed that partially DER variable had negative and insignificant effect, NPM variable had significant negative effect, and EPS variable had positive significant effect. Simultaneously variable DER, NPM, and EPS have an effect on signifikan to stock price. DER, NPM, and EPS variables can explain the stock price variables in chemical manufacturing companies listed in Indonesia Stock Exchange 2010-2016 at 38.9%. Keywords: Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Earning Per Share (EPS) and Stock Price.